ABC of asthma - Rees, John , 1949-; Kanabar, Dipak; Pattani, Shriti (ABC series, 2010)
Asthma is a common condition with increasing prevalence. This book covers the advances in practice and methods, with an emphasis on delivery systems, self-dose assessment and delivery of care with different pharmacological approaches.